2022
DOI: 10.3390/su14148624
|View full text |Cite
|
Sign up to set email alerts
|

Coevolution between Terraced Landscapes and Rural Communities: An Integrated Approach Using Expert-Based Assessment and Evaluation of Winegrowers’ Perceptions (Northwest Piedmont, Italy)

Abstract: Terraced landscapes are characterized by many features but are also threatened by abandonment, with the loss of the historical landscape and increased hydrogeological risk. In this research, we developed an innovative integrated approach using expert-based assessment and evaluation of winegrowers’ perceptions to investigate the coevolution between terraced landscapes and rural communities. The aims were as follows: (i) to identify the historical landscape elements, (ii) to identify the landscape dynamics, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Terkenli et al [67] reported that in Valtellina, which is one of the study areas considered in our research, this strategy's link to tourism is considered a priority. Finally, according to Pomatto et al [19], in order to facilitate the dissemination of knowledge about these landscapes outside the systems, it is important to participate in enhancement programs at the supralocal level, both national programs (e.g., National Register of Historical Rural Landscapes for Italy) and international ones (e.g., Globally Important Agricultural Heritage Systems-program of the Food and Agriculture Organization of the United Nations). Finally, the growing demand for experiential tourism needs to be supported at the supralocal level with specific funds and projects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Terkenli et al [67] reported that in Valtellina, which is one of the study areas considered in our research, this strategy's link to tourism is considered a priority. Finally, according to Pomatto et al [19], in order to facilitate the dissemination of knowledge about these landscapes outside the systems, it is important to participate in enhancement programs at the supralocal level, both national programs (e.g., National Register of Historical Rural Landscapes for Italy) and international ones (e.g., Globally Important Agricultural Heritage Systems-program of the Food and Agriculture Organization of the United Nations). Finally, the growing demand for experiential tourism needs to be supported at the supralocal level with specific funds and projects.…”
Section: Discussionmentioning
confidence: 99%
“…According to Gkoltsiou and Mougiakou [18], to ensure the sustainability of terraced landscapes, it is essential to support territorial management choices that apply qualitative assessment tools and involve local stakeholders. Pomatto et al [19] highlighted the importance of the involvement of rural communities in defining landscape strategies for the enhancement of terraced landscapes.…”
Section: Participatory Approaches and Methods For The Development Of ...mentioning
confidence: 99%
“…Mainly statues of saint protectors and patronswere displayed. They were often related to the three basic pillars of the country's economy and prosperity -craft production, trade, and agriculture (Eliade 2006;Gullino et al 2015;Zheng et al 2018;Pomatto et al 2022). Since the time of the first farmers, the spiritual connection of man with the land is palpable.…”
Section: Introductionmentioning
confidence: 99%